Analytical modelling of CO2 reduction in gas-diffusion electrode catalyst layers. (10th October 2021) - Blake, J.W.; Padding, J.T.; Haverkort, J.W.
Highlights: Analytical approximation of cathodic catalyst layer local environment and reactions developed. Model verified with both numerical and experimental results. Freely accessible spreadsheet of analytical model supplied. Parametric study performed to determine optimal catalyst layer thickness. Graphical abstract: Abstract: The electrochemical reduction of CO 2 on planar electrodes is limited by its prohibitively low diffusivity and solubility in water. Gas-diffusion electrodes (GDEs) can be used to reduce these limitations, and facilitate current densities orders of magnitude higher than the limiting current densities of planar electrodes. These improvements are accompanied by increased variation in the local environment within the cathode, with significant effect on Faradaic efficiency. By developing a simple and freely available analytical model of a cathodic catalyst layer configured for the production of CO, we investigate the relationships between electrode reaction kinetics, cell operation conditions, catholyte composition and cell performance. Analytical methods allow us to cover parameter ranges that are intractable for numerical and experimental studies. We validate our findings against experimental and numerical results and provide a derivation and implementation of the analytical model.